Penerapan Logika Fuzzy Logic pada Enemy AI Game Horor 3D The Gate Of Nightmare Menggunakan Aplikasi Unity3d: Array - Hafizh, Faisal; Maulita, Yani; Khair, Husnul (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2020)
Artificial Intelligence is a part of computer science that is made so that machines (computers) can do work as well as what humans do. The Unity 3D application is a game engine which is a software for processing images, graphics, sound, input, etc. which is intended to create a game, although not always for games. Nowadays, games have developed a lot according to traditions and times. Therefore, there are a lot of unattractive game designs because the AI is not responsive and feels stiff, and requires the Fuzzy Logic Method. Fuzzy Logic is a problemsolving control system methodology that is suitable for implementation in systems, ranging from simple systems, small systems, embedded systems, PC networks, multi-channel or workstation based data acquisition, and control systems.